THE EFFECT OF BRAND AWARENESS AND BRAND TRUST ON CONSUMERS SPORTSWEAR BRAND EXTENSION ATTITUDE AT THE HILL FITNESS CENTER MANADO - Mantik, Tirza (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2013)
Brand is the name, term, design, symbol, or any other feature that identifies one seller’s product distinct from those of other sellers. To introduce a product to the public, company should make a strong brand to increase the consumers’ attitude of sportswear. In order to support an ad in providing information and attract the attention of the public, a company will use brand awareness and brand trust. Research objectives are to analyse the effect of brand awareness and brand trust on consumers’ sportswear brand extension attitude. This research used quantitative analyze by using questionnaires and used Multiple Regression analyze. The population observed is people who are member at The Hill Fitness Center Swissbell Hotel Manado with sample as many as 60 respondents. Results and conclusions show that brand awareness and brand trust have significant effect on brand extension attitude while in the case of simultaneous effect. Brand awareness has a significant partial effect on consumers brand extension attitude while brand trust has no significant partial effect on consumers brand extension attitude and to analyse the simultaneously and partially effect on consumers brand extension attitude, it is better to use brand awareness as a variable to measure consumers sportswear brand extension attitude. However, the analysis result has no proof to show the effect of brand awareness and brand trust on consumers brand extension attitude. Keywords: brand awareness, brand trust, consumers brand extension attitude